Strength training for fat loss - Tumminello, Nick (Human Kinetics, 2024)
"This book contains scientifically founded training principles, nutritional practices, and organizational strategies for successful fat loss training. It explains how to use the three Cs of metabolic strength training-circuits, combinations, and complexes-to accelerate metabolism and maximize fat loss while keeping or building muscle. It details effective exercises and well-rounded workout protocols targeting fat loss that can be done in the gym, at home, and with or without equipment"--Provided by publisher.